STUDI PERBANYAKAN VEGETATIF TANAMAN TAKA (TACCA LEONTOPETALOIDES (L.) KUNTZE) DAN POLA PERTUMBUHANNYA - Wawo, Albert Husein; Lestari, Peni (Research Center for Biology-Indonesian Institute of Sciences, 2015)
Polynesian arrowroot (Tacca leontopetaloides), taka, is one of the tuberous plants that distributed near the sea shore to 220 m above sea level. Taka produces two kind of tubers, parent tuber and peripheral tuber. Local people in several locations used taka for forages, cakes, cosmetics and woven. This plant is a minor crop comodity in Indonesia, so it is not widely cultivated yet, and no informations about taka propagation method and its cultivation. Taka produces both tuber and seed for regeneration propose. Aim of this study was to investigate vegetative propagation of taka and its growth pattern. Results showed that propagation by parent tuber required 24 weeks after sowing to produce new peripheral tuber. Material propagation from new peripheral tuber will become new plant. This new plant will produce next generation tuber in 5 months later. Propagation by peripheral tuber (from field exploration) required 24 -28 weeks after sowing to produce next generation plant with leaves and flower stalk directly. Stolon and the next generation tuber were also produced. Taka tuber can be harvested when its leaf turned yellowish.